Coloring as meaning-making: Exploring developmental dimensions in early childhood art activities - Wahdah Zakiyatun Nisa; Purnomo, Heri (Universitas Islam Negeri Raden Intan Lampung, 2026)
Background: Coloring activities in early childhood education often considered to be simple art activities but could instead represent powerful markers of child development. Nevertheless, most of these studies focused on coloring activity through piecemeal perspective on development and little attention has been given to their role as a continuum of integrated indicators of children's development. Coloring displays physical coordination, symbolism and values being formed as aspects connected with more real learning contexts. Objective: This study seeks to investigate the function of children's coloring activities as visual manifestations of developmental processes in early childhood education. Methods: This qualitative exploratory study employed a fixed comparative characterisation methodology to analyse authentic preschool children artworks in their classroom environment. The analysis of visual data obtained from the children's drawings being used these drawings to delineate reliable characteristics of physical and mental development in the computed visual representations of construction activities. Result: The qualitative analysis indicates there are three major developing areas, each interrelated. Firstly, fine motor development demonstrated as stroke control, pressure adjustment, and spatial coordination. Secondly, Visual-Symbolic representation: Visual choice of colours, rigid shapes remaining the same appendage, symbolic semantic colouring. Third, moral-cognitive meaning-creation is indicated by deliberate color choices that are based on perceived guidelines, context, or values. Conclusion: Findings from drawing activities help to reveal more about integrated developmental domains of children rather than talents alone. It highlights the importance of reflective observation, dialogic engagement, and accounting for the importance of children's visual narratives in art-based learning settings, and positions coloring as an important marker of early-childhood development as well as an important tool for child-centred speech.